Xuanqing Hefa formula relieves sepsis-triggered acute lung injury by targeting the NLRP3/Caspase-1 pyroptosis mechanism - Lei, Can; Zhao, Chunxia; Li, Xucheng; Wang, Kangli; Cen, Tianfen; Liu, Qingquan; Xu, Xiaolong; Zhang, Jun (Frontiers in Immunology, 2026)
IntroductionAcute lung injury (ALI), frequently triggered by sepsis, is characterized by severe respiratory distress and high mortality, particularly in critically ill or elderly individuals. Xuanqing Hefa formula (XQHF) has been clinically applied to alleviate ALI by reducing pulmonary inflammation; however, its underlying mechanisms remain poorly understood. This study aimed to evaluate the therapeutic effects of XQHF on sepsis-induced ALI using both in vitro and in vivo models, and to explore its potential mechanisms of action.Materials and methodsMultiple active constituents of XQHF were identified using UPLC-MS/MS. To investigate the therapeutic potential of XQHF against sepsis-induced lung injury, a cecal ligation and puncture (CLP) model was established in mice, while an in vitro pyroptosis model was developed using lipopolysaccharide (LPS) and Nigericin (Nig) stimulation in Immortalized bone marrow-derived macrophages (iBMDMs). The protective effects of XQHF were evaluated through seven-day survival analysis, histopathological examination of lung tissue, pulmonary wet-to-dry weight ratio assessment (W/D), and quantification of total protein in bronchoalveolar lavage fluid (BALF). In addition, inflammatory responses and cellular injury were assessed via ELISA, oxidative stress assays, lactate dehydrogenase (LDH) release, and immunofluorescence staining. The anti-pyroptotic effects of XQHF were further elucidated using western blotting and flow cytometry.ResultsThe results demonstrated that XQHF significantly preserved lung tissue architecture by attenuating both inflammatory responses and oxidative stress, thereby improving the survival rate of septic mice. At the molecular level, XQHF inhibited the expression of key pyroptosis-related proteins. Similar protective effects were observed in the LPS + Nigericin-induced pyroptosis model in iBMDMs, where XQHF also reduced apoptosis. Confocal microscopy further confirmed that XQHF markedly decreased the expression of pro-inflammatory cytokines, including IL-1β and IL-18.ConclusionsOur results suggest that the therapeutic effects of XQHF may be attributed to the synergistic actions of its multiple active constituents, which collectively suppress the inflammatory cascade and attenuate pyroptosis, thereby alleviating lung injury. Furthermore, both in vivo and in vitro experiments demonstrated that XQHF modulates sepsis-induced acute lung injury, at least in part, through the inhibition of the NLRP3/Caspase-1-dependent pyroptosis signaling pathway.